In the name of the great work: Stalin's plan for the transformation of nature and its impact in Eastern Europe - Olšáková, Doubravka (The environment in history : international perspectives, 2016)
Beginning in 1948, the Soviet Union launched a series of wildly ambitious projects to implement Joseph Stalin's vision of a total "transformation of nature." Intended to increase agricultural yields dramatically, this utopian impulse quickly spread to the newly communist states of Eastern Europe, captivating political elites and war-fatigued publics alike. By the time of Stalin's death, however, these attempts at "transformation"-which relied upon ideologically corrupted and pseudoscientific theories-had proven a spectacular failure. This richly detailed volume follows the history of such projects in three communist states-Poland, Hungary, and Czechoslovakia-and explores their varied, but largely disastrous, consequences.